Noun Phrase Complexity: Influence of L1 (Mandarin) on L2 (English) Academic Writing - Xiao Li; Kit Yee Tang (The English Teacher, 2022)
Noun phrase (NP) complexity can be examined through the types of noun modifiers and phrasal features used in a specific NP. This study intends to address the gap focusing on the NP complexity of students with similar proficiency levels, taking into consideration the possible influence of the syntactic structure of their L1. The analytical model of this study made use of the Hypothesized Developmental Stages for Noun Phrase Modification (Biber et al., 2011). Data examined in this study were academic writings from the master students of University of Malaya (UM), who major in Linguistics or English Language studies. Of the five essays examined, 855 complex NPs were identified. The attributive adjective was found most frequently with 395 occurrences in total. Despite being competent users of the English language, NPs of higher complexity stages were not found abundantly across all the essays. Complex NPs of the lower stages like attributive adjective (47.1%), nouns as pre modifiers (12.2%), of phrases as post modifiers (19.7%), prepositions other than of (concrete/locative meanings) / (abstract meanings) (5.1% / 4.8%) remained as some of the most-frequently used NPs. This study implicates that although students are competent users of the English language, the L1 still has an influence on their essay writing.